Inquiry-based teaching and Forensic Sciences: possibilities to scientific literacy (Research, Society and Development, 2022)
The science teaching from the perspective of scientific literacy, seeks, beyond to provide students with the learning of scientific knowledge, to providing an understanding about the modes of production and legitimization of such knowledge, as well as its relationships with society and the environment, throughout of its technologies. The engagement of students in inquiry-based activities has been considered a fundamental means to promote scientific literacy. In this paper, based on a bibliographical study, we present a discussion about the potential of inserting content from forensic sciences as themes for investigative activities in school. Considering that the forensic sciences already have an investigative character in themselves, we also consider the possibilities that open up for students to become involved in the practices of an applied science, appropriating scientific knowledge, in addition to realizing it in situations that they see themselves in their day-by-day lives, combining social and environmental aspects. Added to this, the motivation of students to engage in activities and the opportunity to learn more about the work of experts and this area of knowledge that is so important in contemporary society.